Provisioning of dental health in public hospitals: A case study of District Jalandhar, Punjab - Shaveta Menon (Wolters Kluwer Medknow Publications, 2016)
Background: The Government of India is increasingly emphasizing the provisioning of dental services in public hospitals, but the rural and deprived sections are struggling to get basic dental procedures done in public hospitals. Aim: To study variations within and across public hospitals for provisioning of dental health settings in Jalandhar district of Punjab. Settings and Design: The study area consisted of four Community Health Centers (CHCs) and District Hospital situated in Jalandhar, Punjab, India. Materials and Methods: The dental infrastructure and dental procedures performed in the public hospital were checked with the help of a checklist as listed in the Indian Public Health Standards 2012 for CHCs and district hospital, and then, the variations within and across these public hospitals were compared. Statistical Analysis: Percentages were used to make comparisons within and across the public health institutions. Results and Conclusions: The results showed that out of total outpatient department (OPD) of the public hospitals, dental OPD formed 5%-10% in public hospitals and extraction was the most frequently performed procedure. There is no availability of prosthodontic and orthodontic procedures in the public hospitals. There were no dental auxiliaries in the CHCs, and there was lack of proper dental materials needed in the dental clinics.